Caracterização e variabilidade espacial de Atributos Físicos em um Argissolo Amarelo no estado do Ceará. - Cajazeira, João Paulo (2007)
The objective of this research was characterize and determine to spatial variability of physical attributes of a Alfisols, using methods geostatistical e and making of surface maps for the method of Kriging, in two soil depths. They were made soil collections in regular intervals of 2.5 m, in an area of 400 m2, being 81 points in each one of the layers (0 – 0.2 m and 0.2 – 0.4 m), to add 162 samples that were submitted to the physical determinations and the obtained data analyzed by the descriptive statistics to verify the normality of the frequency distribution and later on submitted to the geostatistical. The model that better it was adjusted to the curve of the semivariogram, in most of the variables, it was the spherical. However, for the variable density of the particles and aggregate with diameter 2.00-1.00 mm, in the depth of 0 – 0.2 m and flocculation degree, bulk density and soil-water content with tension 1.5 MPa, in the depth of 0.2 – 0.4 m the most appropriate model that better adjusted it was the exponential. The nugget ratio for the flocculation degree, bulk density and density of the particles was of 100%, characterizing “random variance”, confirming the independence of the data. The largest ranges were observed in the depths of 0.2 – 0.4 m for lime percentage (51.00 m) and percentage of sand (35.06 m). The values of the bulk density were considered relatively high being of 1.69 and 1.65 Mg.m-3 for 0 – 0.2 and 0.2 – 0.4 m, respectively. There was a larger humidity retention in the inferior layers.